WORKSHOP ANALISIS DATA KUANTITATIF DAN KUALITATIF UNTUK AKADEMISI DAN PROFESIONAL - Nuning Trihadmini; Siti Saadah; YB Suhartoko; Stanislaus S. Uyanto; Teresia Angelia Kusumahadi (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Problems with data processing and analysis capabilities often hinder lecturers and students in producing research work. Likewise, employees in the financial sector perform data processing in order to support their tasks, namely being able to analyze data into strategic information for the company. The problem solving is carried out by the Master of Applied Economics Study Program, Faculty of Economics and Business, Atma Jaya Catholic University of Indonesia, Jakarta, by organizing a Quantitative and Qualitative Data Analysis Workshop for students, lecturers,  and financial practitioners. The activity starts from July 19 to August 19, 2022. Learning media is held online through Zoom Meetings. The participants of this activity are lecturers and students from various institutions/universities throughout Indonesia, from the University of North Sumatra to the University of Ottow Geissler Papua, as well as from practitioners of financial institutions. The number of applicants for this Data Analysis Training is 558 participants.  Workshop material is an introduction to regression analysis & multivariate modeling (data stationarity,ARDL, ECM, cointegration), univariate modeling (ARMA / ARIMA), Volatility modeling (GARCH), Logistics Regression Analysis, VAR, Panel Data Analysis, data analysis with R Studio, Multivariate statistical analysis (PCA, Discriminant, Cluster Analysis) and path analysis (Path Analysis). Based on the evaluation of the participants, this workshop is very useful for them and it is hoped that there will be a follow-up workshop